PERAN GURU DALAM MENGASAH BAKAT SENI MUSIK ANAK - Tyas, Ratih Sukmaning; Roosmawati, Putri Rahayu Surya Dewi; Rahmawati, Rahmawati (Ibtidaiyyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Early childhood education is the most basic education that occupies a very strategic position in the development of human resources. In shaping children into reliable individuals, parents and teachers have a role in honing children's talents. To hone and develop creativity, interests and talents, it can be started from early childhood. Art talent is a special talent that a person has. The development of children's artistic talents is the duty of teachers in the school environment. Music education as a field of study that has the aim of equipping students to develop personal abilities. This article aims to explain how the role of a teacher in honing musical talent for early childhood to help children's growth and development. The teacher's role includes the types of musical activities to be carried out, characteristics, learning processes, and the influence of music on early childhood development. ABSTRAK Pendidikan anak usia dini merupakan pendidikan yang paling mendasar menempati posisi yang sangat strategis dalam pengembangan sumber daya manusia. Dalam membentuk anak menjadi pribadi-pribadi handal, orang tua dan guru memiliki peran dalam mengasah bakat anak. Untuk mengasah dan mengembangkan kreativitas minat serta bakat maka dapat dimulai sejak anak usia dini. Bakat seni merupakan bakat khusus yang dimiliki seseorang. Pengembangan bakat seni yang dimiliki anak merupakan tugas guru dalam lingkungan sekolah. Pendidikan seni musik sebagai salah satu bidang studi yang memiliki tujuan membekali siswa untuk mengembangkan kemampuan pribadi. Artikel ini bertujuan untuk menjelaskan tentang bagaimana peran seorang guru dalam mengasah bakat seni musik untuk anak usia dini untuk membantu pertumbuhan dan perkembangan anak. Adapun peran guru meliputi jenis-jenis kegiatan musik yang akan dilakukan, karakteristik, proses dalam pembelajaran, serta pengaruh musik pada perkembangan anak usia dini.